“That Which is Measured Improves”: A Theoretical and Empirical Review of Self-Monitoring in Self-Management and Adaptive Behavior Change - Jessica, A. Chen; Eliot, Fearey; Ronald, E. Smith (Journal of Behavior Therapy And Mental Health, 2017)
Current psychological treatment approaches that rely on time-intensive, face-to-face psychotherapy are not capable of meeting the demand for mental health services. Mental health interventions that promote self-regulation and self-management of symptoms will play an increasingly important role in the well-being of millions of individuals. Self-monitoring is a core assessment and intervention component of many mental health interventions and an obligatory first step in the self-regulation process. The present paper reviews prominent theories of self-regulation and describes classic studies spanning clinical, social, cognitive, and personality psychology, which identify potential mechanisms underlying self-monitoring. At the empirical level, we describe the use of self-monitoring across a range of behavioral interventions directed at mental health and physical outcomes, identify factors that influence the effects of self-monitoring, and suggest ways in which technology can be incorporated into these interventions to improve the reach of psychological interventions.
Keywords: self-monitoring; self-management; self-regulation; technology; behavior change